THE CONCEPT AND HISTORY OF MACHINE TRANSLATION - Б.Е., Mұсaғaлиевa; Е.А., Ахaпов (Journal of Oriental Studies, 2019)
Today, machine translation is one of not much linguistically studied areas. The proposed article provides chronological information about the concept of machine translation and the history of its devel opment. The proposed concept of machine translation is based on the concept of translation in general and the theory of translation. The history of the development of machine translation was described on the basis of the works of Russian and other foreign scientists. The classification of the history of machine translation provided by the American scientist J. Hutchins was used, and each stage was supplemented with the necessary information.The purpose of the article is to acquaint the reader with the concept and history of the development of machine translation and provide basic information on the topic. The proposed work may help to famil iarize with the field of machine translation, or to supplement the existing knowledge to readers engaged in applied linguistics and translation studies. It will also help identify and analyze many historical events that led to the formation of machine translation systems. Key words: Machine translation, translation, history of machine translation, Georgetown experi ment, machine translation systems.